Peptide chain release factor DIG8 regulates plant growth by affecting ROS-mediated sugar transportation in Arabidopsis thaliana - Zhang, Xiangxiang; Han, Yuliang; Han, Xiao; Zhang, Siqi; Xiong, Liming; Chen, Tao (Frontiers in Plant Science, 2023)
Chloroplasts have important roles in photosynthesis, stress sensing and retrograde signaling. However, the relationship between chloroplast peptide chain release factor and ROS-mediated plant growth is still unclear. In the present study, we obtained a loss-of-function mutant dig8 by EMS mutation. The dig8 mutant has few lateral roots and a pale green leaf phenotype. By map-based cloning, the DIG8 gene was located on AT3G62910, with a point mutation leading to amino acid substitution in functional release factor domain. Using yeast-two-hybrid and BiFC, we confirmed DIG8 protein was characterized locating in chloroplast by co-localization with plastid marker and interacting with ribosome-related proteins. Through observing by transmission electron microscopy, quantifying ROS content and measuring the transport efficiency of plasmodesmata in dig8 mutant, we found that abnormal thylakoid stack formation and chloroplast dysfunction in the dig8 mutant caused increased ROS activity leading to callose deposition and lower PD permeability. A local sugar supplement partially alleviated the growth retardation phenotype of the mutant. These findings shed light on chloroplast peptide chain release factor-affected plant growth by ROS stress.